Implementation of Profile Matching in Evaluating Customer Satisfaction for PT. BKZ Expedition Services - marfuah, marfuah; Adam, Steffi; Husin, Abdullah; Tanjaya, David (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Evaluation of service satisfaction is essential for decision-making related to efforts to improve service quality. PT. BKZ’s expedition service conducts customer satisfaction evaluations as part of its competitive strategy. The satisfaction assessment for PT. BKZ's import goods delivery service is carried out using five criteria: Reliability, Responsiveness, Assurance, Empathy, and Tangibles. The evaluation process employs the Profile Matching method, which functions to identify the competency gap between actual data values and the predefined profile benchmarks. The questionnaire was distributed online and filled out by PT. BKZ customers. The results indicate that the implementation of the Profile Matching method is effective in supporting decision-making related to service improvement and enhancement strategies at PT. BKZ. The three lowest-scoring criteria that require follow-up action are Empathy (38), Assurance (38.65), and Responsiveness (39.3). These aspects must be improved, particularly among frontline staff at PT. BKZ. The next policy direction should focus on maintaining current staff performance and providing motivation to foster continuous improvement. This can be achieved by offering performance-based bonuses to employees with the highest service satisfaction evaluation scores and providing training programs for those with the lowest performance scores.